Remission, treatment failure, and relapse in pediatric ALL: an international consensus of the Ponte-di-Legno Consortium - Buchmann, Swantje; Schrappe, Martin; Baruchel, Andre; Biondi, Andrea; Borowitz, Michael; Campbell, Myriam; Cario, Gunnar; Cazzaniga, Giovanni; Escherich, Gabriele; Harrison, Christine J; Heyman, Mats; Hunger, Stephen P; et al. (Blood, 2022)
Comparison of treatment strategies in de novo pediatric acute lymphoblastic leukemia (ALL) requires standardized measures of efficacy. Key parameters that define disease-related events, including complete remission (CR), treatment failure (TF; not achieving CR), and relapse (loss of CR) require an updated consensus incorporating modern diagnostics. We collected the definitions of CR, TF, and relapse from recent and current pediatric clinical trials for the treatment of ALL, including the key components of response evaluation (timing, anatomic sites, detection methods, and thresholds) and found significant heterogeneity, most notably in the definition of TF. Representatives of the major international ALL clinical trial groups convened to establish consensus definitions. CR should be defined at a time point no earlier than at the end of induction and should include the reduction of blasts below a specific threshold in bone marrow and extramedullary sites, incorporating minimal residual disease (MRD) techniques for marrow evaluations. TF should be defined as failure to achieve CR by a prespecified time point in therapy. Relapse can only be defined in patients who have achieved CR and must include a specific threshold of leukemic cells in the bone marrow confirmed by MRD, the detection of central nervous system leukemia, or documentation of extramedullary disease. Definitions of TF and relapse should harmonize with eligibility criteria for clinical trials in relapsed/refractory ALL. These consensus definitions will enhance the ability to compare outcomes across pediatric ALL trials and facilitate development of future international collaborative trials.